Effect of a Pheromone on Stress‐Associated Reactivation of Feline Herpesvirus‐1 in Experimentally Inoculated Kittens. (8th December 2017) - Contreras, Elena T.; Hodgkins, E.; Tynes, V.; Beck, A.; Olea‐Popelka, F.; Lappin, M.R.
Abstract : Background: Stress contributes to reactivation of feline herpesvirus‐1 (FHV‐1). The usage of pheromones to decrease stress in FHV‐1 experimentally inoculated kittens has not previously been investigated. Hypothesis/Objectives: To determine whether a feline pheromone would lessen stress, resulting in decreased recurrence of FHV‐1‐associated illness in kittens. Animals: Twelve 5‐month‐old, purpose‐bred kittens. Methods: Randomized, double‐blind, placebo‐controlled clinical trial. Kittens previously infected with the same dose of FHV‐1 were randomized into 2 separate but identical group rooms. After a 2‐week equilibration period, a diffuser containing either the pheromone or placebo was placed in each of the rooms, and the kittens acclimated for an additional 2 weeks. Every 2 weeks thereafter, for the 8‐week study period, housing was alternated between kennel‐ and group housing. Blinded observers applied a standardized clinical and behavioral scoring rubric daily. After each 2‐week period, serum cortisol concentrations and quantitative PCR for FHV‐1 and glyceraldehyde 3‐phosphate dehydrogenase (GAPDH) ratios were evaluated. Clinical, behavioral, and laboratory test results were compared between groups within individual and combined study periods. Results: Sneezing occurred more frequently in the placebo group during individual ( P  = 0.006) and combined study periods ( P  = 0.001). Sleep at the end of observation periods occurred more frequently in the pheromone group during individual ( P  = 0.006) and combined study periods ( P   <  0.001). Conclusions and Clinical Importance: The findings suggest that the pheromone decreased stress, and the decrease in stress response may have resulted in decreased sneezing associated with FHV‐1.